High-intensity activity profiles of elite soccer players at different performance levels - Bradley, P. S.; Di Mascio, M.; Peart, D.; Olsen, P.; Sheldon, B. (The Journal of Strength and Conditioning Research, 2010)
The aims of the study were to (a) determine the high-intensity activity patterns of soccer players at different performance levels and playing positions, (b) investigate temporary and end game fatigue in elite domestic and international soccer matches, and (c) quantify acceleration and maximal running speed profiles of elite soccer players. Elite domestic (n = 100) and international (n = 10) soccer players were analyzed using a multicamera computerized tracking system. No differences were found for high-intensity running distance (2,520 ± 678 vs. 2,745 ± 332 m), mean recovery time (67 ± 15 vs. 71 ± 26 seconds), or maximal running speed (7.76 ± 0.31 vs. 7.66 ± 0.34 m·s-1). The distance covered in high-intensity running irrespective of playing level was 18% lower (p < 0.05) in the last than in the first 15-minute period of the game (391 ± 117 vs. 478 ± 141 m). The decline in high-intensity running immediately after the most intense 5-minute period was similar between international (222 ± 33 vs. 109 ± 37 m or 51% decline) and elite domestic (243 ± 81 vs. 114 ± 51 m or 53% decline) players. Wide midfielders, central midfielders, fullbacks, and attackers covered a greater (p < 0.01) distance in high-intensity running than central defenders (3,243 ± 625, 2,949 ± 435, 2,806 ± 408, 2,618 ± 745 vs. 2,034 ± 284 m). Results demonstrate that high-intensity running is reduced during various periods of elite soccer matches, and high-intensity activity profiles and fatigue patterns are similar between international and elite domestic players but vary markedly between playing positions. These data provide valuable information to the fitness coach regarding the high-intensity active profile of elite soccer players that could be used to develop soccer-specific training drills.